THE MAKING OF LANGUAGES AND NEW LITERACIES: SAN ANDRÉS-PROVIDENCE CREOLE WITH A VIEW ON JAMAICAN AND HAITIAN - Bartens Angela (UNIV ANTIOQUIA, DEPT LINGUISTICA & LITERATURA, 2025)
The aim of this paper is to examine the idea of "language making" and new literacies in creole languages with a focus on San Andres-Providence Creole English. Jamaican and Haitian Creole are taken as points of comparison for their more advanced state of consolidation. Posts from Facebook groups gathered between February 2016 and July 2020 as the main source of data were complemented by 2015 data on San Andres linguistic landscapes. The main finding is that, due to a favorable change in language attitudes both locally and globally, San Andres-Providence Creole is entering into the domain of writing.